Hannah Arendt : liberdade e democracia - Fortes, Dalila Mazzarolo (My University, 2024)
The present dissertation aims to introduce de concepts of political freedom and democracy in the work of Hannah Arendt, sustaining the relations between the two concepts and their relevancy on understanding the reach of the Arendtian concept of action. The first chapter explains the concepts of thinking, will, and judge, then explores the difference between public sphere and private sphere, allowing the discussion about action. The second chapter is divided in two parts: the first is dedicated to the contextualization of positive liberty and negative liberty and the connections to the Arendtian concept of political freedom, followed by second part, discussing the types of democracy, and the work of Hannah Arendt about the concept constitutio libertatis and her thoughts about councils and citizen participation. [resumo fornecido pelo autor]
A presente dissertação visa apresentar os conceitos de liberdade política e democracia na obra de Hannah Arendt (1906-1975), sustentando as relações entre os dois conceitos e sua relevância para a compreensão do alcance do conceito arendtiano de ação. O primeiro capítulo explica os conceitos de pensamento, de vontade e de juízo, em seguida explora a diferença entre esfera pública e esfera privada, permitindo a discussão sobre a ação no sentido político. O segundo capítulo está dividido em duas partes: a primeira é dedicada à contextualização da liberdade positiva e da liberdade negativa e das conexões destas com o conceito arendtiano de liberdade política, seguida da segunda parte, discutindo os tipos de democracia, e ainda a obra de Hannah Arendt no tocante ao conceito constitutio libertatis, e, por fim, as reflexões arendtianas sobre os conselhos e a participação cidadã. [resumo fornecido pelo autor]
Keywords: Arendt, Hannah, 1906-1975; Espaços públicos; Democracia; Liberdade; Ciência política - Filosofia; Public spaces; Democracy; Liberty; Political science - Philosophy